Organizational Commitment in Tourism: Roles of Work Involvement, Organizational Justice, and Job Satisfaction - Alfato Yusnar Kharismasyah; Suharnomo Suharnomo; Mahfudz Mahfudz (Al-Qalam Institute, 2026)
Organisational commitment remains a critical issue in the tourism industry because employee retention and service quality depend heavily on employees' attitudes toward their organisations. Although previous studies have examined organisational commitment extensively, limited attention has been given to the simultaneous roles of work involvement and organisational justice in relation to job satisfaction in tourism organisations. This study aims to examine the effects of work involvement and organisational justice on organisational commitment, with job satisfaction serving as a mediating variable. A quantitative approach was employed, using data collected from 112 employees at Owabong Waterpark in Indonesia. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4.0. The findings reveal that work involvement and organisational justice significantly enhance both job satisfaction and organisational commitment. Job satisfaction also has a significant positive effect on organisational commitment and partially mediates the relationships between work involvement, organisational justice, and organisational commitment. These findings support Social Exchange Theory by demonstrating that employees who perceive fair treatment and actively engage in their work develop greater job satisfaction, which subsequently strengthens organisational commitment. This study contributes to the organisational behaviour literature by extending the application of Social Exchange Theory in the tourism sector and providing empirical evidence on the mediating role of job satisfaction.